Transmittance measurement of the in vivo human eye with a double-pass system - Sánchez, Roberto Francisco (2021)
Purpose: To develop a methodology based on a double-pass system to obtain information about the transmittance of ocular media. Methods: The procedure consists of recording double-pass images at different powers of a laser diode of 780 nm and determining the scattering in an area between 25 35 arcmin of each image. The scattering showed linear behavior in respect to the irradiance of the laser, and the slope of the linear fit was proportional to the transmittance squared of the media evaluated. An artificial eye with different filters was tested first. Then, fifteen subjects with clear ocular media were divided into two groups: Ten subjects classified by the iris color were recruited for the measurements of an ocular transmittance index and the estimation of the transmittance (group A), and another five subjects were selected for measurements with neutral filters (group B). Results: The measurements performed in group A presented a mean transmittance of 42.95%. No differences in the transmittance were found between subjects with different iris color ( p = 0.154). Measurements in group B showed a good correlation (r = 0.959, p < 0.001) between the expected and the measured value for the transmittance. Conclusion: We proposed and evaluated a method to determine the transmittance of the eye in vivo using the double-pass system.